Mitophagy in gastrointestinal tumors: mechanisms and new targets for immunotherapy - Zhang, Tao; Ren, Zhetan; Tang, Bowen; Man, Ru; Wang, Lin; Wang, Qingyan; Peng, Jirun; Yu, Yongduo (Frontiers in Oncology, 2026)
Gastrointestinal tumors (GITs), particularly gastric and colorectal cancers, are the leading causes of cancer-related deaths worldwide. Despite advances in screening technologies and the continuous development of treatments, which have improved early diagnosis and therapeutic interventions, the morbidity and mortality rates remain high, presenting a significant challenge to global public health. While existing treatments can extend patient survival to some degree, they are often accompanied by substantial side effects. In recent years, immunotherapy has yielded positive outcomes for some patients. However, the emergence of immune escape mechanisms has hindered treatment effectiveness. As a result, there is an urgent need for new therapeutic strategies that can address the limitations of current approaches. mitophagy, a key cellular process, has gained significant attention in cancer research. It plays an essential role in maintaining cellular energy balance and metabolic stability, and is intricately linked to crucial biological processes such as drug resistance, metastasis, invasion, and the tumor microenvironment. This article aims to provide a comprehensive review of the mechanisms underlying mitophagy, examining its role in gastrointestinal cancers, particularly in relation to cellular metabolism, apoptosis, drug resistance, metastasis, invasion, and the tumor microenvironment. Additionally, it will explore the potential of mitophagy as a therapeutic target and address current clinical challenges. It is hoped that this research will offer new insights and directions for the treatment of GITs.